Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
Introduction Microsatellite instability (MSI) has broad biologic and clinical relevance across solid tumors, yet its role in sarcomas remains poorly defined. We delineate the clinicopathologic, molecular, and treatment-response landscape of MSI in sarcomas using the largest clinically sequenced cohort to date. Experimental design MSI status was assessed in 6,449 bone and soft tissue tumors, including 5,992 sarcomas from 5,162 patients, using targeted next-generation sequencing and validated bioinformatic pipelines. Results Forty-one sarcomas (0.7%) were MSI-high (MSI-H), comprising 31 soft tissue and 10 bone sarcomas. All exhibited complex genomic profiles, except for one Ewing sarcoma. Pleomorphic sarcomas predominated, mainly undifferentiated pleomorphic sarcoma (UPS) and pleomorphic rhabdomyosarcoma (PRMS) followed by radiation-associated sarcoma. Subtype-specific analysis revealed the highest frequencies of MSI-H in PRMS (4/11, 36%) and radiation-associated sarcomas (6/24, 25%). Tumor mutational burden was higher in MSI-H sarcomas than microsatellite-stable sarcomas but lower than MSI-H carcinomas, while mismatch repair mutational signatures were comparable. Somatic MMR alterations were the primary mechanism (62%), most commonly involving MLH1; MSH2 and MLH1 predominated in Lynch syndrome-associated cases. TP53 (83%) and NF1 (51%) were frequent somatic co-alterations. Among 11 patients treated with immune checkpoint inhibitors (ICI), 3 achieved durable clinical benefit of more than 6 months. PD-L1 expression was higher in responders, whereas alterations in immune-modulator genes were observed in some non-responders. Conclusions MSI is rare in sarcomas (<1%) but enriched in pleomorphic sarcomas, particularly PRMS, and radiation-associated sarcoma. Universal MMR screening of these subtypes may identify candidates for ICI and reveal underlying Lynch syndrome, although responses remain heterogeneous and require further studies.